Pore fluid substitution effects on elastic wave propagation in Berea sandstone: Implication to seismic monitoring of CO2 geologic storage. (March 2022) - Yun, Aryong; Song, Insun
Highlights: Pore fluid substitution from H2 O to CO2 in Berea sandstone leads to a significant change in P-wave form: the amplitude decay and the phase lag occurs. Hysteresis in the P-wave characteristics takes place during a gradual substitution between drainage and imbibition. Seismic velocity can be estimated from the effective elastic moduli of the mixture. The velocity also depends on the distribution of the two fluids as well as their volumetric fractions. Time-lapse seismic records are sufficient for detecting subsurface CO2 plume. Abstract: This study presents an experimental demonstration of seismic monitoring of CO2 geologic storage based on the observation of pore fluid substitution effects on elastic wave propagation along a core sample of Berea sandstone. Two-phase core flooding of distilled water (H2 O) and supercritical carbon dioxide (scCO2 ) was characterized with ultrasonic measurements along a sample in subsurface conditions (750‒800 m depth). Our experimental results show that the compressional (P) wave propagation was clearly sensitive to the pore fluid substitutions between CO2 and H2 O; however, the shear (S) wave was not. The dynamic bulk modulus of water-saturated samples was considerably higher than that of dry or CO2 -saturated samples with ∼22% porosity, whereas little variation was seen in the dynamic shear modulus, regardless of pore fluids. Changes in P-wave velocity, amplitude, and phase were observed during the gradual substitutions of pore fluids; however, no clear changes were seen in the S-wave. Hysteresis in the P-wave characteristics occurred between drainage and imbibition, which was likely due to the different wettability of the two fluids. The characteristics also depend on the distribution (parallel or serial) of the two fluids in the sample as well as the volumetric fractions of the fluids. Thus, no unique relationship exists between the seismic characteristics and the CO2 saturation degree, rather it also depends on the capillary pressure and the compressibility ratio of the two fluids. Our results suggest that time-lapse seismic records are satisfactory for detecting subsurface CO2 plume appearance and migration, however, supplementary data are required for quantitative prediction of CO2 volumetric distribution in the plume.